Standard of Care and Liability of Public Procurement Officials: Blessing or Curse? - Allison Megan Anthony (Obiter, 2019)
Section 217 of the Constitution provides that organs of state, when contracting for goods or services, should do so in accordance with a system that is fair, equitable, transparent, competitive and cost-effective. Therefore, public procurement officials acting on behalf of such organs of state should act in terms of these principles. When their conduct falls foul of section 217, it may be declared unlawful by a court of law. In the recent past, there have been countless reports of unexplained corruption, theft and fraud committed by public officials, especially in the public procurement sector. Consequently, the legislature, by enacting legislation (specifically the new Public Audit Amendment Act 5 of 2018), and the judiciary, by imposing cost orders, have started holding public procurement officials personally liable for unlawful conduct. This article examines the latest developments in this area of law, including case law and recent legislative amendments, and asks the question whether the standard of care and liability of public procurement officials has increased because of these developments.